EVALUASI PRAKTIK AUDIT ATAS UTANG LANCAR PADA KAP XYZ BERDASARKAN STANDAR AUDIT - Inayah Apriasti; Gagah Rayi Farius; Azmi Siti Fauziah; Anindya Radhwa Nurshafiyyah; Ridwan Zulpi Agha (PT. Saha Kreasi Indonesia, 2025)
This study aims to evaluate the audit practices implemented by Public Accounting Firm (KAP) XYZ in the audit of current liabilities, with a focus on compliance with SA 500, SA 501, and SA 505. Current liabilities accounts have the potential for misstatement, either due to understatement or fictitious debt (overstatement). This study uses a qualitative methodology with interviews with KAP XYZ auditors as primary data to assess the stages of implementation, objectives, mechanisms, and compliance of procedures with audit standards. The results show that the audit practices of current liabilities have met most of the requirements of Auditing Standards. The vouching procedure uses a materiality-based sample (approximately 70%-80% of the total account value) and confirmations are carried out in a controlled manner using the positive confirmation method, which successfully increases the reliability of evidence related to the Existence assertion. The main conclusion is that KAP XYZ's audit practices have demonstrated compliance with SA 500 in practice. However, there is room for improvement in the aspects of the independence of confirmations and the identification of contingent liabilities. Further research is recommended to conduct comparative studies involving several Public Accounting Firm of different scales to identify variations in audit procedure.